Analysis of genome-wide variants through bulked segregant RNA sequencing reveals a major gene for resistance to Plasmodiophora brassicae in Brassica oleracea. Issue 1 (December 2018) - Dakouri, Abdulsalam; Zhang, Xingguo; Peng, Gary; Falk, Kevin; Gossen, Bruce; Strelkov, Stephen; Yu, Fengqun
Abstract Two cabbage (Brassica oleracea ) cultivars 'Tekila' and 'Kilaherb' were identified as resistant to several pathotypes ofPlasmodiophora brassicae . In this study, we identified a clubroot resistance gene (Rcr7 ) in 'Tekila' for resistance to pathotype 3 ofP. brassicae from a segregating population derived from 'Tekila' crossed with the susceptible line T010000DH3. Genetic mapping was performed by identifying the percentage of polymorphic variants (PPV), a new method proposed in this study, through bulked segregant RNA sequencing. Chromosome C7 carried the highest PPV (42%) compared to the 30–34% in the remaining chromosomes. A peak with PPV (56–73%) was found within the physical interval 41–44 Mb, which indicated thatRcr7 might be located in this region. Kompetitive Allele-Specific PCR was used to confirm the association ofRcr7 with SNPs in the region.Rcr7 was flanked by two SNP markers and co-segregated with three SNP markers in the segregating population of 465 plants. Seven genes encoding TIR-NBS-LRR disease resistance proteins were identified in the target region, but only two genes, Bo7g108760 andBo7g109000, were expressed. Resistance to pathotype 5X was also mapped to the same region asRcr7 .B. oleracea lines including 'Kilaherb' were tested with five SNP markers forRcr7 and for resistance to pathotype 3; 11 of 25 lines were resistant, but 'Kilaherb' was the only line that carried the SNP alleles associated withRcr7 . The presence ofRcr7 in 'Kilaherb' for resistance to both pathotypes 3 and 5X was confirmed through linkage analysis.